EQUILIBRIUM POINT OF A SUPPLY CHAIN NETWORK COMPRISING DISASTER RELIEF MODEL VIA VARIATIONAL INEQUALITY PROBLEM - Petrot, N.; Tangkhawiwetkul, J. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2022)
In this paper, the supply chain network equilibrium model which composites of the disaster relief part is constructed. In such model, we consider five tiers of decision makers: manufacturers who produce the products for sale and donation, retailers, demand market who can purchase products, freight service providers who transport the relief items (or the products) to demand points and, finally, the demand points. The behavior of all decision makers is considered by using the variational inequality formulation. Furthermore, the qualitative properties of such model are studied. Finally, we give some numerical supply chain examples of such model.